The Impact of Chronic Exposure to Manganese on Testiculaire Tissue and Sperm Parameters in Rat Wistar - BOUDOU, Farouk; Adli, Djallel Eddine Houari; Miloud, SLIMANI; BERROUKCHE, Abdelkrim (International Journal of Natural Sciences Research, 2014)
Aim: To assess the effect of chronic manganese chloride exposure on testis and sperm parameters. Methods: Twenty four male rats, 6 months old, were divided in 2 groups. 12 rats in the lot exposed to manganese, were watered by water containing manganese chloride tetrahydrate (MnCl2 4H2O) at dose of 4.79 mg.ml-1 for 12 weeks. And the group of control male rats received distilled water in the same conditions. The effects on the testicular histology, sperm concentration and percentage of abnormal sperm morphology were observed. Results: After a chronic exposure, microscopic examination of the testes showed degeneration of the seminiferous tubules and the gremlin cell. Seminal parameters indicated a decrease in the sperm levels (21.3 10 6 ±0.96 10 6 cells / ml) compared to the control group (62.70 10 6 ± 3.22 10 6 cells / ml) and a rise of morphological abnormalities (66.1 % ±2.93 %) compared to the control rats (10.83 % ±1.30 %). Conclusion: The present study demonstrated that long-term manganese chloride exposure may have a direct deleterious effect on fertility and reproduction functions of male rats.